Irradiation-catalysed degradation of methyl orange using BaF2–TiO2 nanocomposite catalysts prepared by a sol–gel method - Yongsheng Ling; Guang Wang; Ting Chen; Xionghui Fei; Song Hu; Qing Shan; Daqian Hei; Huajun Feng; Wenbao Jia (Royal Society Open Science, 2019)
BaF2–TiO2 nanocomposite material (hereinafter called the composite) was prepared by a sol–gel method. The composite surface area, morphology and structure were characterized by Brunauer–Emmett–Teller method, X-ray diffraction analysis and a scanning electron microscopy. The results showed that BaF2 and TiO2 form a PN-like structure on the surface of the composite. Composites were used to catalyse the degradation of methyl orange by irradiation with ultraviolet light, γ-rays and an electron beam (EB). It was demonstrated that the composite is found to be more efficient than the prepared TiO2 and commercial P25 in the degradation of methyl orange under γ-irradiation. Increasing the composite catalyst concentration within a certain range can effectively improve the decolorization rate of the methyl orange solution. However, when the composite material is used to catalyse the degradation of organic matter in the presence of ultraviolet light or 10 MeV EB irradiation, the catalytic effect is poor or substantially ineffective. In addition, a hybrid mechanism is proposed; BaF2 absorbs γ-rays to generate radioluminescence and further excites TiO2 to generate photo-charges. Due to the heterojunction effect, the resulting photo-charge will produce more active particles. This seems to be a possible mechanism to explain γ-irradiation's catalytic behaviour.